Direct Mannich‐Type Reactions Promoted by Frustrated Lewis Acid/Brønsted Base Catalysts. Issue 44 (30th September 2016) - Chan, Jessica Z.; Yao, Wenzhi; Hastings, Brian T.; Lok, Charles K.; Wasa, Masayuki
Abstract: Direct Mannich‐type reactions that afford both α‐ and β‐amino esters by the reaction of a broad range of carbonyl compounds and aldimines are disclosed. The transformation is promoted by a sterically frustrated Lewis acid/Brønsted base pair, which is proposed to operate cooperatively: Within the catalyst complex, an enolate is generated that then reacts with a hydrogen‐bond‐activated imine. Noncovalent interactions between reactants and the catalyst provide selectivity and new opportunities for future catalyst design. Abstract : It pays to be direct if you're frustrated : A sterically frustrated Lewis acid/Brønsted base pair was found to serve as a potent cooperative acid/base catalyst for direct Mannich‐type reactions (see scheme; EDG=electron‐donating group, PG=protecting group). An array of ketone, ester, amide, and thioester pronucleophiles underwent enolization by the catalyst and reaction with aldimines to afford both α‐ and β‐amino esters.